2017
DOI: 10.2217/fon-2017-0165
|View full text |Cite
|
Sign up to set email alerts
|

County level incidence rates of chronic lymphocytic leukemia are associated with residential radon levels

Abstract: Aim:We previously reported that incidence rates for chronic lymphocytic leukemia (CLL) among US states are significantly correlated with levels of residential radon (RR). Because these correlations could be influenced by confounding and/or misclassification among large geographic units, we reinvestigated them using smaller geographic units that better reflect exposure and disease at the individual level.Methods:We examined the relationships between CLL and RR per county in 478 counties with publicly-available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Residential radon levels are especially high in ND [13]. Our structural equation model confirmed that radon levels in homes were significantly associated with uranium measurements in soil.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Residential radon levels are especially high in ND [13]. Our structural equation model confirmed that radon levels in homes were significantly associated with uranium measurements in soil.…”
Section: Discussionsupporting
confidence: 72%
“…These data were compiled from multiple sources, including government records for well permits, state agencies that regulate utility rates, and bills from wastewater treatment facilities and tax appraisers' offices [11]. Data on the uranium contest of soil was from the US Department of Energy [12] and data on indoor radon levels were from the ND State Radon Survey, as described previously [13].…”
Section: Data and Sourcesmentioning
confidence: 99%
“…Data on uranium levels in soil are from the U.S. Department of Energy [18]. Radon levels per county are from the state radon monitoring research program conducted in the 1980s, as described previously [19]. Data for I-131 levels for individuals in ND counties were obtained from the NCI website [20].…”
Section: Methodsmentioning
confidence: 99%
“…The number of lung cancer deaths caused by radon far exceeds the number of deaths from more-publicized dangers, e.g., drunk driving (17,400) [2]. Indeed, the death toll from lung cancer likely underestimates radon's force of mortality as radon also causes potentially fatal non-malignant lung disease, e.g., interstitial lung fibrosis [3] and may contribute to death from other cancers, e.g., chronic lymphocytic leukemia [4,5] and malignant melanoma [6].…”
Section: Introductionmentioning
confidence: 99%